Upaya Penanggulangan Tindak Pidana Korupsi Dalam Pengadaan Barang dan Jasa di Indonesia - Prasetio, Lilik (Pusat Strategi Kebijakan Penegakan Hukum, Kejaksaan Agung, 2024)
Corruption in procuring goods and services has become a crucial problem that hampers development in Indonesia. The high potential for deviations in this process requires effective and sustainable efforts to overcome it. This study aims to identify strategic steps in preventing and prosecuting corruption in this sector. This paper uses legal research methods, namely normative legal research and empirical juridical. Several stages that have the potential for deviations in the procurement of goods and services, some of which include Deviations in the Budget Planning and Negotiation Stages, Deviations in the Tender Process, Deviations in the Implementation of Work and Project Handover, Payment Patterns